Robotic versus open liver resections: A case‐matched comparison. Issue 3 (6th January 2017) - Morel, Philippe; Jung, Minoa; Cornateanu, Sorina; Buehler, Leo; Majno, Pietro; Toso, Christian; Buchs, Nicolas C.; Rubbia‐Brandt, Laura; Hagen, Monika E.
Abstract: Background: Most hepatic resections are currently performed using an open approach. Robotic surgery might enable the transition of these procedures to minimally invasive surgery. Methods: Pre‐, peri‐ and post‐operative data of all patients who underwent a liver resection from 2009/2012 to 2001/2015, were collected prospectively. All robotic resection patients were matched 1:1 to patients who underwent open surgery. Pre‐ and perioperative data, up to 30 days, were analyzed. Results: Sixteen robotic and open hepatic resections were identified. Fewer complication events and shorter lengths of stay (LOS, 7.9 versus 11 days, P = 0.0603) were observed for robotic resections. Length of stay in the intermediate care unit (IMC) was shorter after the robotic procedure (10 h vs 16.6 h, P = 0.0699). Operating room (OR) time was significantly longer in the robotic resection cohort (352.8 vs 239.6 min, P = 0.0215). All tumor margins were negative. Conclusions: This preliminary comparison demonstrates the general feasibility of minor robotic liver resection in selected cases.